Feasibility of heating metal implants with alternating magnetic fields (AMF) in scaled up models. (31st December 2022) - Sadaphal, Varun; Prasad, Bibin; Kay, Walker; Nehring, Lisa; Nyugen, Trung; Tepper, John; Tanner, Melissa; Williams, Dustin; Ashton, Nicholas; Greenberg, David E.; Chopra, Rajiv
Abstract: Aim: Treatment of infected orthopedic implants remains a major medical challenge, involving prolonged antibiotic therapy and revision surgery, and adding a >$1 billion annual burden to the health care system in the US alone. Exposure of metallic implants to alternating magnetic fields (AMF) generates heat that can provide a noninvasive means to target biofilm adhered to the surface. In this study, an AMF system with a solenoid coil was constructed for targeting a metal plate surgically implanted in a sheep model. Methods: A tissue-mimicking phantom of the sheep leg was developed along with simulation model of phantom and the live sheep leg. This was used evaluate heating with the AMF system and to compare experimental results with numerical simulations. Comparative AMF exposures were performed/simulated in these model for feasibility of design, verification, and validation of simulations. Results: The system produced magnetic field strengths up to 12mT and achieved plate temperatures of 65–80 °C within 10–14 s. Single and intermittent AMF exposures of a tissue-mimicking phantom agreed with numerical simulations within 5 °C. Similar agreement between experimental measurements and simulations was also observed in the live sheep metal implant model. The simulations also predicted 2–3 mm of tissue damage using a CEM43 thermal dose model for 1-h AMF exposures targeting 65 °C for pulse delays of 2.5 and 5 mins. Conclusion: This study confirmed that AMF technology can be scaled up to treat implants in a large animal model with the same rates of heating and peak temperatures achieved in prior in vitro studies. Further, numerical simulations provided accurate predictions of the heating produced by AMF on metal implants and surrounding tissues, and can be used to design AMF coils for treating human prosthetic joint implants with more complex geometrical shapes.